Role of brain serotonin in modulating fish behavior - Winberg, Svante (Curr Zool, 2016)
The organization of the brain serotonergic system appears to have been highly conserved across the vertebrate subphylum. In fish as well as in other vertebrates, brain serotonin (5-HT), mainly acts as a neuromodulator with complex effects on multiple functions. It is becoming increasingly clear that acute and chronic increase in brain 5-HT neurotransmission have very different effects. An acute 5-HT activation, which is seen in both winners and losers of agonistic interactions, could be related to a general arousal effect, whereas the chronic activation observed in subordinate fish is clearly linked to the behavioral inhibition displayed by these individuals. Fish displaying divergent stress coping styles (proactive vs. reactive) differ in 5-HT functions. In teleost fish, brain monoaminergic function is also related to life history traits.